Intrinsic and Extrinsic Analysis of “The Little Prince” by Antoine de Saint-Exupéry - Dimas Bayu Pratama; Bastian Sugandi (Papanda Publisher, 2025)
This article aims to analyze the novel The Little Prince by Antoine de Saint Exupéry through intrinsic and extrinsic elements. This article analyzes qualitative methods with a descriptive approach. This study focuses on four aspects: theme analysis, character analysis, plot and setting analysis, and extrinsic context including the author's historical background. From the results of the analysis, 4 elements were found: (1) prominent themes in the novel The Little Prince, such as loneliness, friendship, love, and the serch for meaning; (2) the development and nature of his unique character; (3) The author's reflection on his life, especially when he was a pilot and faced the harshness of war, greatly influenced the depth of meaning and symbols scattered throughout his narrative; and (4) moral and existential messages conveyed through the story. Through contemplative reading, the researcher found that the harmony between the intrinsic elements and the author's life background created layers of emotion and messages that transcended cultural boundaries. This study proves that qualitative literary analysis is not only a tool to appreciate the beauty of language, but also a window to understand the human values that live in it.